The application of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model to understand the acceptance and usage of SIMAK UNIGA (Case study: Digital Business program in the Faculty of Economics) - Diqy Fakhrun Shiddieq (RISTEC : Research in Information Systems and Technology, 2023)
The application of information and communication technology is often not achieved due to the unwillingness of users to accept and use the existing system. The purpose of this study was to analyze the relationship between the determinant factors of SIMAK utilization on the user's behavioral intention, to analyze the relationship between habit and facilitating condition factors to user behavior, and to analyze the relationship between user behavior intention and user behavior. This study used a quantitative method by conducting a questionnaire survey to Digital Business Study Program student, Garut University. Measurements were carried out using the UTAUT 2 model construct, then testing was carried out with the Structural Equation Model (SEM) and SPSS. This finding proves that 1) performance expectancy, effort expectancy, social influence, facilitating condition, and hedonic motivation have no effect on behavioral intention. 2) habit and trust in information have an effect on behavioral intention. 3) habit and facilitating conditions have no effect on user behavior. 4) behavioral intention has an effect on user behavior. The implications of this research can be considered in the application of information and communication technology in improving performance.